Everyday Sadism as a Predictor of Rape Myth Acceptance and Perception of Harassment - Saravia Lalinde, Ivonne Alicia (International journal of offender therapy and comparative criminology, 2023)
The #MeToo movement has stressed the need to understand why individuals who witness sexual violence may or may not take action. However, prevention programs usually fail to address the association between personality traits and attitudes, perception, and behavior in the context of sexual violence. To improve prevention programs’ effectiveness, it is vital to understand how personality traits might interfere with willingness to engage in bystander intervention. This study aims to explore the relationships between Everyday Sadism, perception of harassment, Rape Myths and gender in a sample of 177 participants recruited online. Analyses revealed significant gender differences, with men endorsing more Rape Myths, perceiving less harassment, and being more sadistic. Gender and everyday sadism emerged as significant predictors of perception of harassment. In the case of Rape Myths, age emerged as an additional predictor. These results have several implications, ranging from expanding our knowledge of the influence of everyday sadism on factors known to modulate bystander behaviors as well as informing and shaping the development of prevention programs.